2017
DOI: 10.1515/plc-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Strategies for School Writing Tasks: A Cross-Cultural Report

Abstract: We investigated cross-cultural differences in ninth-grade students' reported use of self-regulated strategies for writing. We assessed 12 self-regulated strategies for writing tapping environmental, behavioural, and personal self-regulated processes. Seven hundred and thirty-two Portuguese and Brazilian students in transition to high school (M age = 14.3; 372 male and 306 female) from mainstream urban schools reported on their use of the strategies. Statistical analyses included a multivariate analysis of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In line with this study, Sanad (2014) also concluded that self-regulated learning contributed to the development of writing skills depended on students' selfevaluation, self control, and self-reinforcement. Further, a cross cultural report was investigated in relation with self-regulated strategies for school writing task in which it implies different type of strategies of the students to regulate their writing affected by different cultural backgrunds and gender diversity (Malpique, Simao, & Frison, 2017). In addition, self regulation was assessed with writing beliefs and epistemology of pre-service teachers in their academic writing task, and their beliefs about learning writing were indicated to have important role in their selfregulation behaviours (Hammann, 2005).…”
Section: Self-regulated Learning In Academic Writingmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this study, Sanad (2014) also concluded that self-regulated learning contributed to the development of writing skills depended on students' selfevaluation, self control, and self-reinforcement. Further, a cross cultural report was investigated in relation with self-regulated strategies for school writing task in which it implies different type of strategies of the students to regulate their writing affected by different cultural backgrunds and gender diversity (Malpique, Simao, & Frison, 2017). In addition, self regulation was assessed with writing beliefs and epistemology of pre-service teachers in their academic writing task, and their beliefs about learning writing were indicated to have important role in their selfregulation behaviours (Hammann, 2005).…”
Section: Self-regulated Learning In Academic Writingmentioning
confidence: 99%
“…In other words, students regulate their writing behaviour through some strategies. Revision is one of the units of writing personal strategies aside from planning, organizing, self-evaluating, recalling/creating mental images, time planning, readers' awareness (Zimmerman, 1989;Malpique et al, 2017). Further help-seeking as social/environmental strategy is also deployed to regulate the students' self regulation in writing processes.…”
Section: Self-regulated Revision On Academic Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that male and female ELED students are not significantly different in implementing SRL strategies in academic writing. It means that the students in this research experienced what Shen and Bai [34] argued the difference between believing that gender is only a biological construct and believing that gender is a social construct may explain the non-significant gender effects. Moreover, gender differences in SRL disappear when gender stereotypes or beliefs about gender are considered [35].…”
Section: Discussionmentioning
confidence: 90%
“…Specifically, for this study, it is relevant to understand the interventions developed based on the process approach. One of the lines that has made the most progress in this regard is the one on teaching strategies (Harris et al, 2011;Malpique, Veiga, & Frison, 2017), focused on integrating self-regulation and writing in intervention programs. Scientific evidence has demonstrated that teaching strategies has achieved a significant impact on the writing performance of students with different levels of schooling.…”
Section: Introductionmentioning
confidence: 99%